Geoarchaeological and 3D visualisation approaches for contextualising in-situ fossil bearing palaeokarst in South Africa: A case study from the ∼2.61 Ma Drimolen Makondo. (30th July 2018) - Herries, Andy I.R.; Murszewski, Ashleigh; Pickering, Robyn; Mallett, Tom; Joannes-Boyau, Renaud; Armstrong, Brian; Adams, Justin W.; Baker, Stephanie; Blackwood, Alex F.; Penzo-Kajewski, Paul; Kappen, Peter; Leece, AB; et al.
Abstract: South Africa contains a wealth of palaeokarst deposits that have yielded hominin fossils and Early Stone Age archaeology. Despite the complex nature of deposition within many of these caves there has been a dearth of detailed geoarchaeological studies undertaken on these sites. Many sites in South Africa have been interpreted using an overly simplistic Member System based on simplified sedimentological attributes, rather than chronostratigrahic units. Many of the defined Members thus identify different, but contemporary geological processes occurring in the caves. This has caused serious confusion in reconstructing the life histories of palaeocaves and the ages of the fossil remains interned within them. It is critical to uncover new sites that have not been extensively altered by decades of data collection and destructive mining techniques employed early in their discovery. Although unmined sites present their own problems with regards to extensive colluvium cover and access to fossil-bearing units, analysing strata that is found in-situ enhances overall confidence of interpretations drawn. A wealth of geoarchaeological and 3D visualisation techniques can now be employed to aid in the understanding of cave life histories, as well as their excavation. In this paper we present the first attempt to integrate and publish data from a range of such methods on South African fossil bearing palaeokarst using the newly discovered Drimolen Makondo deposit as a case study. This includes the use of ground penetrating radar, 3D visualisation through photogrammetry and multi-scale 3D scanning, micromophology and petrography, palaeomagnetism, mineral magnetism, synchrotron radiation, electron spin resonance, uranium-lead dating and biochronology. Our analysis has allowed us to successfully uncover the full extent of this new ∼2.61 Ma fossil bearing palaeokarst deposit and to visualise and interpret its chronostratigraphy.